Studying and Improving Treatment of Calprotectin, Helicobacter Pylori and Interleukin-6 in Blood of Patients with Covid-19 (Journal of Pharmaceutical Negative Results, 2022)
Of the 100 patients who were followed up, 60 were "relatively cured" of Covid-19 and 40 were uninfected. The levels of calprotectin, Helicobacter pylori and interleukin-6 in the blood, which were detected in their feces, were reliably higher in those who passed the coronavirus. At the next stage of the study, the patients of the first group were divided into 2 subgroups of 30 based on the complex treatments prescribed on the basis of the standard of treatment of the existing disease. The first subgroup was prescribed rebamipide as a combination therapy and compared with the other two groups. In the group that received rebamipide, compared to those that did not receive it, it was found that calprotectin, Helicobacter pylori and interleukin-6 in the blood were significantly reduced.